Exercise addiction and COVID-19-associated restrictions - Lim, M. A. (Journal of Mental Health, 2021)
The coronavirus disease 2019 (COVID-19) pandemic has brought a new reality in every area, including sports. The shutting down of gyms, swimming pools, and fitness centres, postponement of sporting events, and closure of non-emergency physical therapy services, along with the practice of self-isolation, quarantine, and social distancing, as well as restrictions on outdoor activities and exercises, may eventually have physical, psychological, and behavioural consequences to the population. Under such unusual circumstances, many individuals struggle to maintain physically active lifestyles. Therefore, alterations in habits and routine activities, including mobility, exercise, and physical activity, are necessary.